2022
DOI: 10.1158/1535-7163.mct-22-0313
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Photoimmunotherapy Targeting Podoplanin-Expressing Cancer Cells and Cancer-Associated Fibroblasts

Abstract: Near-infrared photoimmunotherapy (NIR-PIT) is a new cancer treatment that utilizes an antibody-IRDye700DX (IR700) conjugate that binds to a target followed by the application of NIR light that results in dramatic changes in solubility of the conjugate leading to rapid cell membrane damage and highly immunogenic cell death. NIR-PIT has been used clinically in treating advanced head and neck cancers using an anti-epidermal growth factor receptor (EGFR) antibody-IR700 conjugate and has been conditionally approved… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Our previous studies reported no significant increase in intratumoural Treg populations after NIR-PIT. 25 , 39 Thus, we further assessed the migration of immunosuppressive cells including Tregs and MDSCs from the TDLN to the tumour three days after hEGFR-targeted NIR-PIT using mEERL-hEGFR tumour models. Twenty-four hours after 780 nm light irradiation, the percentage of Cy5-labeled Tregs and MDSCs was comparable between the NIR-PIT and No NIR-PIT groups ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies reported no significant increase in intratumoural Treg populations after NIR-PIT. 25 , 39 Thus, we further assessed the migration of immunosuppressive cells including Tregs and MDSCs from the TDLN to the tumour three days after hEGFR-targeted NIR-PIT using mEERL-hEGFR tumour models. Twenty-four hours after 780 nm light irradiation, the percentage of Cy5-labeled Tregs and MDSCs was comparable between the NIR-PIT and No NIR-PIT groups ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that higher PDPN expression is associated with poorer outcomes in human colorectal carcinomas [59] and is considered to be another promising method of targeting CAFs [60]. Aside from high expression on CAFs, PDPN is also highly expressed in lymphatic endothelium, both in normal tissues and during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various therapeutic approaches targeting cancer‐associated fibroblasts (CAFs), including the use of specific antibodies and antibody conjugates with photosensitizers, have been documented. [ 70 , 71 ] BC exhibits a high affinity for endoscopic therapeutic modalities, and targeting CAFs in situ may yield a more effective outcome in inhibiting tumor recurrence. These findings shed light on the regulatory mechanisms involved in recurrent BC and inform the development of new therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%